Microencapsulation of Ruellia tuberosa L. Aqueous Root Extracts Using Chitosan-Sodium Tripolyphosphate and Their In Vitro Biological Activities - Anna Safitri; Anna Roosdiana; Nia Kurnianingsih; Fatchiyah Fatchiyah; Eldina Mayasari; Rina Rachmawati (Scientifica)
The current study aims to perform microencapsulation of R. tuberosa L. extracts using chitosan crosslinked to sodium tripolyphosphate (NaTPP) as wall materials by spray drying and to analyze their in vitro biological activities. The influence of manufacturing conditions, like pH, chitosan concentration, and stirrer time, was assessed. Results showed that microcapsules prepared in pH 4 with a concentration of 0.1% (w/v) chitosan, and 90 min stirring time had 51.80% encapsulation efficiency and high in vitro biological activity. These were shown by high in vitro alpha amylase inhibition and antioxidant activity with IC50 values of 50.65 μg/mL and 123.97 μg/mL, respectively. Releases of the bioactive compounds in microcapsules of R. tuberosa L. were carried out on phosphate buffer medium pH 2.2 and pH 7.4 with times release of 30, 60, 90, and 120 min. The bioactive compounds were released in pH 2.2 in 120 min at 2.48%. At pH 7.4, the active ingredients were more easily released, by 79.90% in 120 min. The microcapsules’ morphology showed a rough surface with spherical forms and the average sizes were 53.41 μm. This study supports the essential role of microencapsulation in improving plant extracts with reserved biological activities.